1986
DOI: 10.1159/000238456
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Co-Trimazine (Sulphadiazine plus Trimethoprim) in Geriatric Patients

Abstract: The study was aimed at analyzing the pharmacokinetics of sulphadiazine (SDZ) and trimethoprim (TMP) in geriatric patients and was carried out in two stages. The first stage compared 11 geriatric patients (68–89 years old) and 9 healthy volunteers (21–34 years old). Serum concentration and urine elimination were determined on day 4 after 12-hourly administration of 1 tablet of co-trimazine containing 410 mg sulphadiazine (SDZ) plus 90 mg trimethoprim (TMP). The mean serum concentrations of SDZ were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…There is information on the pharmacokinetics of various forms of sulfonamides in older subjects; this information was recently reviewed by Ljungberg et al 232 Their review included studies on sulfamethizole, sulfisoxazole, sulfisomidine, sulfadimidine, and sulfadiazine, but not sulfamethoxazole 232 . In a study by Bergan et al, the pharmacokinetics of trimethoprim plus sulphadiazine (sulfadiazine) was investigated in geriatric patients 233 . Their data showed that in older patients TMP serum concentrations were slightly higher and urine excretion was less in comparison with those of young volunteers; the sulfadiazine kinetics were similar.…”
Section: Pharmacology and Pharmacokinetics Of Antibioticsmentioning
confidence: 99%
“…There is information on the pharmacokinetics of various forms of sulfonamides in older subjects; this information was recently reviewed by Ljungberg et al 232 Their review included studies on sulfamethizole, sulfisoxazole, sulfisomidine, sulfadimidine, and sulfadiazine, but not sulfamethoxazole 232 . In a study by Bergan et al, the pharmacokinetics of trimethoprim plus sulphadiazine (sulfadiazine) was investigated in geriatric patients 233 . Their data showed that in older patients TMP serum concentrations were slightly higher and urine excretion was less in comparison with those of young volunteers; the sulfadiazine kinetics were similar.…”
Section: Pharmacology and Pharmacokinetics Of Antibioticsmentioning
confidence: 99%